Aplikasi Pencarian Dokter di Kota Padang Berbasis Mobile - Yance Sonatha; Ervan Asri; Indri Rahmayuni (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Nowadays people have started to realize the importance of health. Everyone wants to quickly find out where the right doctor is if they want to get health services or have shown certain symptoms of illness. This research resulted in an application called "find doctor" which aims to be able to find the location and information of the doctor closest to the user while in the city of Padang. This study adopted stages of the Waterfall Model and was built using the Location Based Service method provided by Android. This application is built from two sides, namely the android client and the web server. This research produces an application that can find the location and information of the desired doctor's practice in the city of Padang. Applications that can be accessed using an internet browser (server) and android smartphone (client) with a minimum Android 5.0 operating system.